2021
DOI: 10.1111/jph.12995
|View full text |Cite
|
Sign up to set email alerts
|

Aggressiveness of Fusarium culmorum isolates for head blight symptoms is highly stable across four cereal crops

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It should be noted that isolate × host genotype interactions have been observed for some Fusarium species and cereal species combinations, but the impact of the interactions were limited compared to the main effects (György et al, 2020;Stenglein et al, 2014). Accordingly, Miedaner et al (2021) observed no isolate × host genotype interactions for different F. culmorum isolates inoculated on several cereal species. Our study included one variety only.…”
Section: Resistance To F Langsethiae and Ht2 + T2mentioning
confidence: 80%
See 1 more Smart Citation
“…It should be noted that isolate × host genotype interactions have been observed for some Fusarium species and cereal species combinations, but the impact of the interactions were limited compared to the main effects (György et al, 2020;Stenglein et al, 2014). Accordingly, Miedaner et al (2021) observed no isolate × host genotype interactions for different F. culmorum isolates inoculated on several cereal species. Our study included one variety only.…”
Section: Resistance To F Langsethiae and Ht2 + T2mentioning
confidence: 80%
“…Aggressiveness and toxin producing ability of F. langsethiae isolates We observed significant differences between isolates in the level of F. langsethiae DNA in harvested grain after inoculation, suggesting variation in aggressiveness in the Norwegian F. langsethiae population. Differences in aggressiveness have been observed within different Fusarium species, such as F. culmorum, F. poae, and F. graminearum (Aamot et al, 2015;Miedaner et al, 2021;Stenglein et al, 2014). For F. langsethiae, variations in aggressiveness have been observed among UK isolates in detached leaf assays, and the aggressiveness was independent of the host from which the isolates originated (Imathiu et al, 2009;Opoku et al, 2011).…”
Section: Resistance To F Langsethiae and Ht2 + T2mentioning
confidence: 99%
“…The study at hand extended thus this concept of a negligible genotype‐by‐species interaction for FHB resistance in wheat to the resistance against the accumulation of the associated mycotoxins. This suggested that wheat breeders need to test their germplasm only for resistance against one Fusarium species, while genotype‐by‐isolate interactions are usually also of negligible magnitude (Miedaner et al, 2021; Serajazari et al, 2019). However, an indirect selection for the mycotoxin content was estimated to be less efficient when using trials inoculated with F. sporotrichioides in comparison to F. graminearum and F. culmorum , since their plot‐based heritability or repeatability was much lower due to a lower aggressiveness of the F. sporotrichioides isolate, leading to lower genetic variation for FHB symptom severity and rendering the precise differentiation between genotypes a more difficult task.…”
Section: Discussionmentioning
confidence: 99%
“…For research purposes, the existing literature applies highly specialized methodologies with enzymes causing resistance in different genotypes. The stability of aggressiveness lasts for a shorter time, being mostly stable for several years [ 143 ] but potentially changing after a longer period. The F. culmorum isolate No.…”
Section: Phenotyping How To Evaluate Resistancementioning
confidence: 99%
“…This is closer to the natural condition, where every infection site is the result of the infection of a single conidium of millions in a field. When the specialized races are absent, the aggressiveness differences between isolates influence resistance differentiation; at higher aggressiveness, the differentiation is much better [ 12 , 95 , 143 ]. For this reason, with four isolates or inocula with differing levels of aggressiveness from medium to high, there is a higher probability of gaining a more reliable result.…”
Section: Phenotyping How To Evaluate Resistancementioning
confidence: 99%